PELAKSANAAN DIPLOMASI DAN KERJASAMA LUAR NEGERI OLEH PEMERINTAH KOTA/KABUPATEN DI KARESIDENAN SURAKARTA - Herning Suryo Kartika Giri (RESEARCH FAIR UNISRI, 2018)
This research aims to explain how the implementation of local government cooperation with foreigncountries or foreign NGO in 2012 until 2017 on around the region of Surakarta. The data of thatkind cooperation was really hard to get in the newspaper and also by search it on the internet,researchers want to collect all of international cooperation by local goverment on around the regionof Surakarta in 2012 until 2017. This is because, with the implementation of local governmentautonomy in Indonesian cities and region, now they can make cooperation with foreign countriesor foreign NGO but must still give priority on Indonesian national interest. Researchers believethat altough we could not get it in internet, international cooperation between local governmentexist. By using the theory and concept of diplomacy, international cooperation and nationalinterest, this research make use of qualitative method with primary data from the interview withlocal government staff in cooperation section and also use document-based research and explainedby descriptive method. Through analysis we concluded that local government on around the regionof Surakarta already have several international cooperation with foreign countries, cities or NGOin 2012 until 2017. But there are still many obstacles in the implementation of MoU or LoI whichalready signed by both parties such as lack of coordination with national government, localgoverment and also agencies which directly involved with international cooperation, lack ofcapabilities in lobbying and negotiation, lack of english, and budgeting problems.Key words: Local Government, Diplomacy, International Cooperation, National Interest